In vivo assessment of brainstem depigmentation in Parkinson’s: potential as severity marker for multi-centre studies - Schwarz, Stefan Theodor; Xing, Yue; Tomar, Pragya; Bajaj, Nin; Auer, Dorothee P. (Radiological Society of North America, 2016)
Purpose: To investigate the pattern of neuromelanin signal intensity loss within the substantia nigra pars compacta (SNpc), locus coeruleus, and ventral tegmental area in Parkinson disease (PD); the specific aims were (a) to study regional magnetic resonance (MR) quantifiable depigmentation in association with PD severity and (b) to investigate whether imaging- and platform-dependent signal intensity variations can be normalized.